Evaluation and comparison of serological methods for the detection of bovine neosporosis in Argentina = Evaluación y comparación de pruebas serológicas para la detección de la neosporosis bovina en Argentina - Campero, Lucía María; Minke, Lieselotte; More, Gastón; Rambeaud, Magdalena; Bacigalupe, Diana; Moore, Prando Dadin; Hecker, Yanina Paola; Campero, Carlos Manuel; Schares, Gereon; Venturini, María Cecilia (Asociación Argentina de Microbiología, 2019)
Neospora caninum is a protozoan parasite that causes abortion and important economic losses in cattle worldwide. The accurate diagnosis of neosporosis is essential for management and control measures. The aims of this study were: i) to evaluate the performance of an in-house enzyme-linked immunosorbent assay based on the 38 kDa native antigen (p38-ELISA) to diagnose bovine neosporosis in Argentina using a well- characterized local sera panel from experimentally infected and naturally exposed cattle and ii) to compare the diagnostic performance and agreement of three N. caninum serological tests: p38-ELISA, indirect fluorescence antibody test (IFAT) and immunoblotting (IB) using the same sera panel. Serum samples testing either positive or negative by IFAT and IB were considered “Relative Standards of Comparison” (RSC) and used for p38-ELISA evaluation. Receiver operating characteristics analysis revealed that p38-ELISA was highly accurate (area under the curve= 0.982) according to RSC with a cut-off index of 0.0905. Relative sensitivity and specificity of p38-ELISA were 97.8 % and 99.5 %, respectively and agreement between RSC and p38-ELISA was almost perfect (k= 0.97). The evaluation and performance comparison of serological tests were performed according to the definition of gold standard based on the decision of the “majority of tests”. All tests displayed high sensitivity and specificity values (greater than 95 %); and excellent agreement. This study describes the accurate performance of p38-ELISA evaluated locally and the highly accurate diagnostic performance of the studied tests for the detection of anti-N. caninum antibodies in cattle from Argentina.